1252 Rapid-onset Obesity with Hypothalamic Dysfunction, Hypoventilation, and Autonomic Dysregulation (ROHHAD) Syndrome in a Patient on Stimulants and Normal BMI at the Time of Diagnosis: A Case Report and Literature Review. (27th May 2020) - McGhee, Vera; Viteri, Ernesto; Schoumacher, Robert; Relia, Sachin; Harris, Atia
Abstract: Introduction: ROHHAD is a rare and complex pediatric disorder presenting in early childhood with rapid onset obesity, followed by central hypoventilation, hypothalamic dysfunction, endocrine disorders, and neurobehavioral disorders. Report of Case: We present a unique case of a 6-year-old girl diagnosed with ROHHAD in the setting of normal Body Mass Index (BMI). Patient had a history of food-seeking behavior, hyperphagia, and rapid onset obesity at the age of 4 years old with subsequent development of autonomic dysregulation, hypoventilation, and neurobehavioral disorders. At the time of evaluation in Sleep Medicine Clinic for snoring and disrupted sleep the patient had been treated for hyperactivity with several appetite-suppressing stimulant medications leading to weight loss and causing her to have a normal BMI. The original polysomnogram demonstrated severe Obstructive Sleep Apnea (OSA) with obstructive Apnea-Hypopnea Index (AHI) of 11.2/hour and was concerning for hypoventilation based on the end-tidal CO2 values and morning blood gas. Despite improvement in OSA with CPAP therapy, the patient's hypercapnia persisted. The overall clinical presentation resulted in extensive multispecialty workup, which ultimately led to the diagnosis of ROHHAD syndrome despite the patient's normal BMI. Conclusion: ROHHAD syndrome is a rare and complex pediatric disorder requiring multi-disciplinary approach, with early diagnosis and intervention being essential for management of the condition. Hypothalamic obesity is one of the diagnostic hallmarks of ROHHAD. However, about half of patients with ROHHAD develop neurobehavioral disorders, which might require treatment with stimulant medications. Literature review revealed several case reports addressing the effect of stimulant medications on hypothalamic obesity, however none focusing on patients with ROHHAD syndrome. This case raises questions about the role of appetite-suppressing medications in the management of obesity in patients with ROHHAD. It also suggests possible need for further specific workup in patients on stimulants with hypoventilation in the absence of obesity.